Respuesta :
[tex]Pull \ out \ like \ factors : \\ \\
42 + 20x = 2 * (10x + 21) \ \\ \\ Solve : \ 2 = \ 0 \\ \\ Subtract 21 from both sides of the equation : \\
10x = -21 \\ \\ Divide both sides of the equation by 10: \\ \\
x = -21/10 = \boxed{-2.100 }
[/tex]
Answer:
The solutions are [tex]x=-5+\sqrt{6}[/tex] and [tex]x=-5-\sqrt{6}[/tex]
Step-by-step explanation:
we have
[tex]2x^{2} +20x=-38[/tex]
Divide by [tex]2[/tex] both sides
[tex]x^{2} +10x=-19[/tex] ------> [tex]x^{2} +10x+19=0[/tex]
we know that
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]x^{2} +10x+19=0[/tex]
so
[tex]a=1\\b=10\\c=19[/tex]
substitute
[tex]x=\frac{-10(+/-)\sqrt{10^{2}-4(1)(19)}}{2(1)}[/tex]
[tex]x=\frac{-10(+/-)\sqrt{100-76}}{2}[/tex]
[tex]x=\frac{-10(+/-)\sqrt{24}}{2}[/tex]
[tex]x=\frac{-10(+/-)2\sqrt{6}}{2}[/tex]
[tex]x1=\frac{-10(+)2\sqrt{6}}{2}=-5+\sqrt{6}[/tex]
[tex]x2=\frac{-10(-)2\sqrt{6}}{2}=-5-\sqrt{6}[/tex]